Inequality, public wealth, and the federal shareholder - Giacomo Corneo (Institute for the Study of Labor (IZA), 2016)
Current trends in the distribution of wealth trigger a social divide and threaten democracy in many advanced economies. I propose to counter this evolution by enhancing the role of public capital as a redistribution and empowerment device. The governance of public capital requires two novel institutions: a socially responsible Sovereign Wealth Fund and a Federal Shareholder. This paper offers an account of their possible design and sources of financing.
Keywords: H0; H5; 330; public ownership; redistribution